2006
DOI: 10.1037/1076-898x.12.4.207
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus-response compatibility with pure and mixed mappings in a flight task environment.

Abstract: The present study examined the stimulus-response compatibility (SRC) effect in a simulated flight environment. Experiments 1 and 2 tested the effect with pure and mixed mappings in flight tasks by using attitude displays with inside-out and outside-in formats, whereas Experiments 3 and 4 used a simplified display and tasks. The SRC effect was obtained with mixed mappings when responses were turns of a flight yoke (Experiments 1-3). In contrast, the SRC effect was absent with mixed mappings when they were butto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
44
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 62 publications
8
44
3
Order By: Relevance
“…In Experiment 1, the type of display (plane-moving or horizonmoving) did not affect performance, and similar results have been reported in previous studies using both display types (Yamaguchi & Proctor, 2006. The display type and the effect produced by the manual rotation (which differed between the display types), however, were completely task irrelevant and may simply have been ignored by the participants (Ansorge, 2002).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…In Experiment 1, the type of display (plane-moving or horizonmoving) did not affect performance, and similar results have been reported in previous studies using both display types (Yamaguchi & Proctor, 2006. The display type and the effect produced by the manual rotation (which differed between the display types), however, were completely task irrelevant and may simply have been ignored by the participants (Ansorge, 2002).…”
Section: Discussionsupporting
confidence: 72%
“…Thus, the squared mean deviation from the horizontal alignment, which is possibly less sensitive than the present measures, was used as the dependent measure. This does not apply, however, to other studies (Yamaguchi & Proctor, 2006 that reported no performance differences between the two display types when manipulated between subjects (compared to the within-subject manipulation in our study). An important difference, however, relates to the stimuli used in previous studies, which were either differently pitched tones or colored visual stimuli (presented laterally).…”
Section: Response-effect Compatibility and Wheel Rotation Responsescontrasting
confidence: 53%
See 1 more Smart Citation
“…Several factors argue against such an account, though. First, when trials of the SRC task with compatible and incompatible mappings are mixed, the SRC effect is eliminated regardless of whether the mapping signal is a centered orientation stimulus (Shaffer, 1965), as in the present study, or a color feature of the imperative stimulus (e.g., Heister & Schroeder-Heister, 1994;Yamaguchi & Proctor, 2006). Second, because the SRC effect is eliminated when either mappings or tasks are mixed (and the signal is the color feature), the absence of effect when mappings and tasks together are mixed is a sensible outcome.…”
Section: Mean Src and Simon Effectsmentioning
confidence: 99%
“…Both the SRC and Simon effects persist across hundreds of trials (e.g., Dutta & Proctor, 1992;Proctor & Lu, 1999) and are obtained for a variety of spatial stimulus and response sets in simple and complex tasks (Proctor & Vu, 2006;Yamaguchi & Proctor, 2006). However, the effects are absent or reversed when the SRC task is performed with compatible and incompatible trials mixed, or when trials from SRC and Simon tasks are mixed (Proctor & Vu, 2002a).…”
mentioning
confidence: 99%